2009
DOI: 10.1007/s11661-009-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferrite and Spheroidized Cementite Ultrafine Microstructure Formation in an Fe-0.67 Pct C Steel for Railway Wheels under Simulated Service Conditions

Abstract: The microstructure development of a high-carbon steel (0.67 pct C) for railway wheels as they are affected by rolling contact with rail tracks and by cyclic frictional heat from braking is studied in the vicinity of the contact surface by scanning electron microscopy (SEM) and electron backscattered diffraction. An ultrafine microstructure consisting of ferrite grains with a size of less than 1 lm and spheroidized cementite particles is formed in the region up to 100 lm below the contact surface. The generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The hypothesis that the nature of the band is localized shear is substantiated by the fact that the ratio of band width to grain size is about (100 nm)/(2 nm) = 50, a ratio that has been observed in shear bands in iron with grain sizes between 80 and 268 nm [39]. One might speculate that these shear bands are associated with former particle-particle boundaries, where the local interparticle friction during HPT and the onset of interparticle bonding leads to a localized microstructure with a completely different appearance, reminding of the famous white etching layers on the surface of railway tracks and wheels [44], where the deformation mechanism is equally a combination of pressure and shear. At the particle-particle boundaries, there cannot be a steady state before the interparticle bonding is secure enough to impede interparticle friction, which will take a longer time than grain size saturation inside (former) particles.…”
Section: Microstructurementioning
confidence: 86%
“…The hypothesis that the nature of the band is localized shear is substantiated by the fact that the ratio of band width to grain size is about (100 nm)/(2 nm) = 50, a ratio that has been observed in shear bands in iron with grain sizes between 80 and 268 nm [39]. One might speculate that these shear bands are associated with former particle-particle boundaries, where the local interparticle friction during HPT and the onset of interparticle bonding leads to a localized microstructure with a completely different appearance, reminding of the famous white etching layers on the surface of railway tracks and wheels [44], where the deformation mechanism is equally a combination of pressure and shear. At the particle-particle boundaries, there cannot be a steady state before the interparticle bonding is secure enough to impede interparticle friction, which will take a longer time than grain size saturation inside (former) particles.…”
Section: Microstructurementioning
confidence: 86%
“…It may be of interest that cracks, similar to head checks with related growth regime, can also be observed in railway wheels, see e.g. reference [26].…”
Section: Discussionmentioning
confidence: 99%
“…1. These deformation/annealing conditions were selected based on the results of preliminary experiments conducted to reproduce the ultrafine microstructure observed in the vicinity of the surface of an actual railway wheel [3]. The microstructure investigation was carried out using scanning electron microscopy on the center region of the axially symmetric deformed specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on surface cracks, we have revealed that microstructure development in the vicinity of the surface, caused by in situ thermomechanical treatment under service conditions, could be one of the key factors affecting mechanical and fatigue properties [3]. The microstructure in the vicinity of the contact surface changes from pearlite in the initial state to an ultrafine microstructure, composed of spheroidized cementite and ferrite with a grain size of less than 1 m, through continuous recrystallization.…”
Section: Introductionmentioning
confidence: 99%